English Instruction for Special Educational Needs: A Narrative Inquiry of a Learning Support Assistant - Ramadhani, Ayu Sinta; Fithriani, Rahma (Language Circle: Journal of Language and Literature, 2022)
In terms of instruction and materials, EFL for children is very different, particularly if it is taught in inclusive classes where children with Special Educational Needs (SEN) are grouped in one class and receive the same education. Therefore, students with SEN require a learning support assistant (LSA) to aid in explaining and guiding their learning. In this study, we will therefore employ a narrative inquiry methodology to describe the experience of an LSA in assisting students in the English language. The collected data were examined using content analysis. Challenges associated with the LSA profession that accompany EFL learning, differences in the educational background of the profession, as well as social relationships and interactions with the school environment are the focus of this study's findings, which are intended to provide other learning support assistants with based-on-experience information.